Carbondioxide absorption capability and stomatal features of tropical lowland native trees - Purnomo, Danang Wahyu; Prasetyo, Lilik Budi; Widyatmoko, Didik; Rushayati, Siti Badriyah; Usmadi, Didi; Wati, Richa Kusuma; Solihah, Saniyatun Mar’atus (Buletin Kebun Raya, 2023)
The selection of native tree species for land rehabilitation and carbon emission reduction is needed in Indonesia. The ability of CO2 absorption is determined by the level of plant adaptation, including the character of the stomata. This study aimed to select native trees species that are effective in absorbing CO2 and evaluate the effect of stomatal characters on carbon absorption capabilities. The tree species were selected based on nativeness, natural habitat in the low lands, large stature, and economic potential. Carbon absorption analysis was carried out by carbohydrates analysis. The variables observed included total leaf area and stomatal characteristics consisting of number, size, and density. The relationship between the predicted variables and absorption was analyzed by linear regression. Our study showed six native tree species have a high potential for CO2 absorption, including Terminalia bellirica (130.17 g/hour), Pterospermum javanicum (61.77 g/hour), Litsea garciae (59.78 g/hour), Anisoptera marginata (54.75 g/hour), Diospyros frutescens (44.64 g/hour), and Canarium vrieseanum (29.69 g/hour). Stomatal area, density, and sample leaf area did not correlate with CO2 sink ability. At the tree scale, the total number of stomata, total stomatal area, and total leaf area had a significant effect (P<0.005) and varied on adding CO2 mass during photosynthesis. The strong effect on CO2 mass occurs in the variable total leaf area (R2=0.698), the combination of the total number of stomata and total leaf area (R2= 0.700), and the combination of the total number of stomata and total leaf area (R2=0.727).